Poking Holes in L.A.’s New Condom Requirement: Pornography, Barebacking, and Speech - Alexander S. Birkhold (Washington University Law Review, 2013)
In November 2012, California voters approved the County of Los Angeles Safer Sex in the Adult Film Industry Act, known as ―Measure B. The law requires producers of erotic adult films to overcome financial hurdles and complete educational training to secure filming permits and also mandates the use of condoms during the production of adult films. If a movie‘s producers shoot a scene involving anal or vaginal intercourse without a condom, they will lose their Measure B permits, face fines, and be forbidden from engaging in any future filming for an unspecified period. Although the purpose of the law is laudable—to minimize the spread of sexually transmitted infections resulting from the production of adult films in the County of Los Angeles—the regulation functions as an outright ban on the filming of unprotected, or bareback, sex scenes and is an impermissible infringement on protected speech. Since Measure B‘s strict requirements do not leave open alternative channels of communication, the law will fail constitutional scrutiny under a content-neutral standard. This conclusion, however, may be difficult to reach if the value of barebacking as speech and the alternative means of expression are only evaluated through a traditional heteronormative lens. Queer theory offers a distinctive platform from which to challenge the law, and a careful analysis of bareback sex within the gay community brings the importance of this speech into sharper relief. Barebacking constitutes a unique identity within the gay community, namely hypermasculinity. Forcing a gay porn star to cover his penis during filming is tantamount to sheathing his sword, blunting his masculinity, power, and speech.
Keywords: Safer Sex in the Adult Film Industry Act; Measure B; barebacking; condoms